Laminin α1 globular domains 4–5 induce fetal development but are not vital for embryonic basement membrane assembly - Schéele, Susanne (National Academy of Sciences, 2005)
During early mouse embryogenesis, each laminin (Lm) chain of the first described Lm, a heterotrimer of α1, β1, and γ1 chains (Lm-1), is essential for basement membrane (BM) assembly, which is required for pregastrulation development. Individual domains may have other functions, not necessarily structural. The cell binding C terminus of Lm α1 chain contains five Lm globular (LG) domains. In vitro, α1LG1–3 domains bind integrins, and α1LG4 binds dystroglycan, heparin, and sulfatides. A prevailing hypothesis is that α1LG4 is crucial as a structural domain for BM assembly, whereas integrin-binding sites conduct signaling. The in vivo role of α1LG4–5 (also called E3) has not been studied. Mice lacking α1LG4–5 were therefore made. Null embryos implanted, but presumptive epiblast cells failed to polarize and did not survive past day 6.5. BM components including truncated Lm α1 were detected in Reichert's membrane. Surprisingly, embryonic BM assembly between visceral endoderm and stem cells was normal in null embryos and in embryoid bodies of α1LG4–5-null embryonic stem cells. Yet, stem cells could not develop into polarized epiblast cells. Thus, α1LG4–5 provides vital signals for the conversion of stem cells to polarized epithelium.